Knowledge and attitude of law, medicine, and mass-communication students towards deceased organ donation: a cross-sectional study from Kathmandu, Nepal - Paneru, Pragya; Budhathoki, Shyam S.; Uprety, Samyog; Yadav, Birendra K.; Mulmi, Rashmi; Sharma, Ikshya (International Journal Of Community Medicine And Public Health, 2020)
Background: With the global increase in the incidence organ failure and subsequent advancement in the medical technology, organ transplantation is growing as the best choice of treatment among the patients with various kinds of organ failure. However, the rate of deceased organ donation is relatively low in South-East Asia regions, including Nepal. This has created a mismatch between the demand and supply of organs for transplantation. World Health Organization encourages organ transplantation from a deceased organ donor as there is no risk to the donor. Thus, this paper aimed to assess knowledge and attitude of literate group specifically towards deceased organ donation. Methods: This was a cross-sectional study conducted among 299 students selected conveniently from medicine, law, and mass communication streams from 9 different colleges (3 colleges from each stream) of Kathmandu. Data was collected through a self-administered questionnaire. Knowledge level was classified into three different categories based on obtained scores and attitude was analyzed based on five-point Likert scale. Results: Almost half (48.8%) of the respondents while only 7% had high level of knowledge on the organ donation and transplantation. Similarly, 95% of the people had positive attitude towards organ donation. However, there was a weak correlation between knowledge and attitude of the respondents. None of the respondents carried an organ donation card. Conclusions: There is a need to plan robust strategies to educate people on organ donation so that they can make pragmatic decisions to register their names for deceased organ donation.